Study on Temporal Variation of Physico-chemical Parameters of Buriganga River Water through GIS (Geographical Information System) Technology (Bangladesh Journal of Scientific and Industrial Research, 2010)
Now a days, Buriganga is one of the most polluted rivers in Bangladesh. Most of the industries and factories of Dhaka are situated on the banks of the Buriganga or very close to the river system. Substantial part of urban sewage of the Dhaka city is also thrown in the Buriganga river. A study was conducted to determine the pollution level of water of Buriganga river. Field investigation was started from June 2004 and Sample collection was conducted six times at an interval of two months up to April, 2005. Different water quality parameters such as pH, EC, TDS, DO, Cations (Na+, K+, Ca2+, Mg2+,NH4+) and anions (HCO3-, Cl-, SO42-, PO43-, NO3-) were examined for water of each sampling points to monitor the level of these parameters where it exceed or within the permissible limit. Present investigation suggested that, Dissolved Oxygen (DO) concentration of water of Buriganga river was very low particularly in dry season (2-3 mg/l). Ammonium (NH4+) and Nitrate (NO3-) concentration near Hazaribagh, Sadarghat, Zinzira, Lalbagh, Kotouali and Shutrapur area were very high, which crossed the maximum permissible limit. In dry season the level of pollution was much high than in wet season. That indicates the water of Buriganga was not safe for drinking purposes, irrigation, fisheries, recreational activities and various industrial uses for most of the times of year. Key words: Buriganga river, GIS technology, Temporal variation DOI: 10.3329/bjsir.v44i3.4406 Bangladesh J. Sci. Ind. Res. 44(3), 327-334, 2009